Antimicrobial Activity of Liquid Soap Containing Turmeric (Curcuma domestica val.) and Lemongrass (cymbopogon nardus l.) Leaf Juice - Erly Sitompul; Nazliniwaty (Talenta Publisher, 2018)
Abstract. The purpose of this study was to formulate an antimicrobial liquid soap containing 25% turmeric and lemongrass leaf juice. Lemongrass leaf juice and turmeric juice 25% were formulated into a liquid soap. Stability, pH and viscosity of the liquid soap were evaluated. For stability tests, the preparation was stored for 3 months at room temperaure. The pH test was measured by Hanna pH meter. The viscosity test,was measured by Brookfield viscometer.The antimicrobial activity of the liquid soap was measured by disc diffusion method using bacteria such as Staphylococcus epidermis, Eschericia coli, Microsporum gypseum and Candida albicans. Physical properties of the formulated liquid soap including pH, viscosity, and stability showed that it was stable for 3 months. The results of antimicrobial test of the liquid soap containing turmeric and lemongrass leaf juice showed that the inhibition diameter against Staphylococcus epidermis, Eschericia coli, Microsporum gypseum and Candida albicans were 22.89, 27.05, 24.30, and 33.05 mm, respectively, while the liquid soap without the juice were 20.76, 19.50, 20.50 and 21.46 mm, respectively. The soap was effective in inhibiting the growth of microbes. Combination of turmeric and lemongrass leaf juice increased the inhibitory zone diameter of the liquid soap for microbe. Keywords: Antimicrobial Agent, Lemongrass Leaf, Liquid Soap, Turmeric Leaf.